TO THE QUESTION ON THE CHOICE OF RADIOTRACER FOR THE DINAMIC NEPHROSCINTIGRAPHY WITH FUNCTIONAL TESTS - D.K. Fomin; T.V. Lepaeva; E.G. Agapov; S.P. Yatsyk; A.V. Ryabtseva; O.A. Borisova; A.A. Nazarov (Педиатрическая фармакология)
The comparison of quality of the images at various stages complex dynamic nephroscintigraphy of the urinary tract received with use of various types of radiotracers. To all patients has been executed dynamic nephroscintigraphy with orthostatic sign and indirect radionuclide cystography, also the analysis of quality of images is lead by a method of expert estimations. It was established, that the best opportunities of a visual estimation of a condition of collective system of kidneys and ureters are provided with application tubular radiotraceres, and for an estimation parenchymatous phases of research — glomerular traceres.Key words: vesicoureteral reflux, secretory function of kidneys, excretory function of kidneys, dinamic scintigraphy, radionuclide cystography.